(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Street vendors are one of the important segments of informal sectors in India. They are generally scattered in urban and rural areas of India. Most of the street vendors are not fully covered by protection and promotion measures. Social security measures are very essential to protect and promote their interests even if a few street vendors are availed social security measures in the study area. The study found that most of the street vendors are not aware about available social security measures.